Qualifications for the Criminal Act of Disseminating Private Chats to Public Spaces from the Perspective of Law Number 1 of 2023 concerning the Criminal Code - Ade Indriani; Fero Sanjaya; Herlita Eryke (PALAR | PAKUAN LAW REVIEW, 2026)
The dissemination of private chats into public spaces has become a growing legal issue in Indonesia's digital environment. Beyond raising concerns regarding privacy, such conduct may also affect an individual's reputation and involve the unauthorized disclosure of personal data. This study analyzes the legal qualifications of disseminating private chats in the perspective of Law Number 1 of 2023 concerning the Criminal Code and examines its relationship with the Electronic Information and Transactions Law and Law Number 27 of 2022 concerning Personal Data Protection. This research employs a normative legal method using statutory, conceptual, and case approaches. Legal materials are analyzed through grammatical, systematic, and teleological interpretation. The findings indicate that the dissemination of private chats cannot automatically be classified as a criminal offense. Criminal liability arises only when the act fulfills specific legal elements, including intentional dissemination, absence of legal justification, infringement of reputation, or unauthorized disclosure of personal data. The study further demonstrates that Articles 433–440 of the Criminal Code, the Electronic Information and Transactions Law, and the Personal Data Protection Law operate in a complementary manner in assessing criminal liability. Accordingly, the dissemination of private chats should be understood as a multidimensional legal issue involving the protection of honor, privacy, and personal data within Indonesia's digital legal framework.   Keywords : Digital Communication, Defamation, Personal Data, Privacy, Private Chats, Criminal Law.